A study on transformation in infant mortality rates in India: mortality indicators as major tool for indicating status of nation’s health - S., Chandramohan Reddy; Reddy, Dharna (International Journal of Contemporary Pediatrics, 2020)
Background: Mortality is important to study population change in the country; infant mortality is considered as principal component balancing the child sex ratio. In this study authors aimed to analyze how mortality rates and child sex ratios are different in urban and rural areas and how its growth statistics are changing over years. Objectives of the study were to quantify infant mortality rates change over time and check the means among mortality indicators. Methods: The study was conducted using secondary data obtained from various issues and reports published by Registrar General and Census Commissioner, India for a period of 10 years from 2006 to 2016. The obtained data on mortality indicators were subjected to basic statistical analysis using percent change and paired t-test. Results: The Infant mortality rate which was reduced by 23 points indicating reduction of 67.65 percent control over a period from 2006 to 2016. Further, results show that, in case of urban mortality, there was significant difference between mortality indicators during study period, the p-value (0.011) was less than level of significance (0.05) so we reject the null hypothesis and it is concluded that there is significant difference between the means of urban mortality indicators over a period of from 2006 to 2016. Conclusions: The infant mortality rate frequently provided as a key indicator of overall the development. There is need for stable child sex ratio; health of children and women are essential for better growth and reaching stable child sex ratio for the ever increasing population.